Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Which equation shows the point-slope form of the line that passes through [tex](3, 2)[/tex] and has a slope of [tex]\frac{1}{3}[/tex]?

A. [tex]y + 2 = \frac{1}{3}(x + 3)[/tex]
B. [tex]y - 2 = \frac{1}{3}(x - 3)[/tex]
C. [tex]y + 3 = \frac{1}{3}(x + 2)[/tex]
D. [tex]y - 3 = \frac{1}{3}(x - 2)[/tex]


Sagot :

To find the equation of a line that passes through a point and has a given slope, we use the point-slope form of the equation of a line, which is given by:

[tex]\[ y - y_1 = m(x - x_1) \][/tex]

Here:
- [tex]\( (x_1, y_1) \)[/tex] is a point on the line.
- [tex]\( m \)[/tex] is the slope of the line.

In this problem, the given point is [tex]\( (3, 2) \)[/tex] and the slope [tex]\( m \)[/tex] is [tex]\( \frac{1}{3} \)[/tex].

Plugging these values into the point-slope form formula:

[tex]\[ y - 2 = \frac{1}{3}(x - 3) \][/tex]

So, the equation of the line in point-slope form that passes through the point [tex]\( (3, 2) \)[/tex] with a slope of [tex]\( \frac{1}{3} \)[/tex] is:

[tex]\[ y - 2 = \frac{1}{3}(x - 3) \][/tex]

Now, let's match this equation with the given options:
- [tex]\( y + 2 = \frac{1}{3}(x + 3) \)[/tex]
- [tex]\( y - 2 = \frac{1}{3}(x - 3) \)[/tex]
- [tex]\( y + 3 = \frac{1}{3}(x + 2) \)[/tex]
- [tex]\( y - 3 = \frac{1}{3}(x - 2) \)[/tex]

Clearly, the equation [tex]\( y - 2 = \frac{1}{3}(x - 3) \)[/tex] matches the form we derived.

Therefore, the correct equation is:
[tex]\[ y - 2 = \frac{1}{3}(x - 3) \][/tex]

Thus, the correct answer is:
[tex]\[ \boxed{y - 2 = \frac{1}{3}(x - 3)} \][/tex]